Decision Dynamics in Two High Reliability Military Organizations - Roberts, Karlene H.; Stout, Suzanne K.; Halpern, Jennifer J. (Management Science, 1994)
In this research we extend theoretical development about decision making in organizations in which many kinds of errors cannot be tolerated. Catastrophic consequences can be associated with faulty decision making in reliability-seeking organizations, a situation which does not occur in most organizations studied in the past. Observations are drawn from two nuclear-powered aircraft carriers. We find decision processes which appear to change often in these organizations. Important decisions can be made by a number of men even at the lowest levels of the organization. Task-related factors such as technical complexity, high interdependence, and catastrophic consequences associated with rare events and more cognitive factors such as accountability and salience affect decision processes. A model is presented that accounts for dynamic change in decision processes in these organizations.